REGULAR FORM SPECIFICATION OF L LANGUAGE DETERMINISTIC AUTOMATA - Чеботарьов, А. М.; Курівчак, О. І. (Science-based technologies, 2009)
Some forms of representation of deterministic automata specifications in the language L are investigated. The use of such forms in the construction of specifications decreases the possibility of errors.